PENINGKATAN HASIL BELAJAR SISWA KELAS 2 PADA MATERI EKSPRESI PERASAAN MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) - Nailul Izzah; Endang Suprapti; Umi Arsiyati (PROCEEDING UMSURABAYA, 2024)
The learning process is a system.achieving process standards to improve the quality of education can begin by analyzing each component that can shape and influence the learning process. However, the component that has long been considered to significantly influence the education process is the teacher. This is indeed reasonable, as teachers are the frontline individuals who directly interact with learners as subjects and objects of learning. In order to achieve learning objectives and manage the classroom to become a solid, communicative, and conducive team during the learning process, a teacher is expected to manage the learning process effectively. Based on this experience, the researcher aims to explore a teaching method that can involve learners more deeply in the learning process, making them interested in studying the Indonesian language and improving their learning outcomes. One solution is to implement the Project Based Learning (PjBL) model. This research uses the Classroom Action Research (CAR) method. Data collection procedures involve written tests and observations. The research results indicate that through the implementation of the Project Based Learning (PjBL) model, there is a significant improvement in the learning outcomes of students in the expression of feelings material, with an increase of 28%.